TiO2 Microwave Synthesis, Electrophoretic Deposition of Thin Film, and Photocatalytic Properties for Methylene Blue and Methyl Red Dyes. (7th April 2014) - Singh, A. K.; Nakate, Umesh T.
Abstract : Electrophoretic deposition (EPD) of TiO2 thin film was carried out at room temperature on low cost steel substrate using microwave synthesized nanoparticles (NPs) of TiO2 . Synthesized NPs and EPD thin film were characterized at different stages of synthesis for its crystal structure, morphology, elemental analysis, and surface area. Spherical particle morphology and formation of TiO2 were confirmed by scanning electron micrograph (SEM), energy dispersive spectrometer (EDS), and X-ray diffraction (XRD). Synthesized NPs were formed in anatase phase having crystallite size of about 12.3 nm from Scherrer's formula using full width half maxima (FWHM). Surface area was found to be 43.52 m 2 /g by BET giving particle size of 33 nm. Photocatalytic (PC) behavior of TiO2 NPs and EPD TiO2 film on steel substrate was investigated under UV light for two commercial dyes and their photocatalysis efficiency was analyzed. NPs have shown better efficiency for methylene blue (MB) dye than EPD film whereas EPD film have shown higher PC activity for methyl red (MR) dye.